ANALISIS STRATEGI BAURAN PEMASARAN PADA USAHA BUDIDAYA IKAN AIR TAWAR CV ALAM JAYA PRIYANGAN - Sari, Anggra Novita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to determine the application of the 7P marketing mix strategy (product, price, place, promotion, people, process, physical evidence) infreshwater fish cultivation businesses in Solam Raya Village. The research method used is a case study with a qualitative research approach. Data collection techniques use observation, interviews and documentation techniques. Analysis of research data by means of data reduction, data presentation and drawing conclusions. The data sources for this research are fish farmers and fish buyers at CV. Alam Jaya Priyangan Solam Raya Village and the data is the result of interviews with fish breeders and buyers. The research results show that there is an application of the 7P marketing mix strategy in CV fish cultivation. Alam Jaya Priyangan Solam Raya Village. Various kinds of products are offered at affordable prices, strategic locations, and promotions are carried out in two ways, namely directly and on social media, the service provided to buyers is very good, with a thorough and neat seeding to delivery process equipped with good supporting equipment.Keywords:Freshwater Fish Culvation; Marketing Mix; 7P